ANALYSIS OF RELATIONS BETWEEN VENDOR MANAGEMENT AND SERVICE QUALITY OF AGENTS A SURVEY OF PT. SYNERGY FIRST LOGISTICS AT TANGERANG 2016 - Tri Mulyani; Andriani Rahmita; Rahmat Hidayat (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2018)
This study was aimed at  measuring  the performance of the Agents and Vendors. To find out whether it is appropriate or not with the lead time the study was using Service Level Agreement based on delivery of goods.  The problems of this research were How the implementation of Vendor Management at PT. Synergy First Logistics was, How the quality of service of the Agent was and What the influence of Vendor Management with service quality Agent was. To solve the problems, the researchers were using two methods.  Data collection methods through Field Research and Library Research.  This research used quantitative analysis to explain the phenomena of the influence between Vendor Management and Service Quality of Agent by collecting numerical data that are analysed using mathematic methods. Based on the result, the correlation shows that vendor management and service quality has a relationship value of 0.708 with significant level 000 that means there is a significant correlation between the two variables.